Proposed Design Improvements for Earplugs Considering the Factors Affecting Their Comfort - Fatima Pulungan, Aqila; Widyanti, Ari (Journal of Research in Industrial Engineering and Management, 2025)
The low compliance with earplug uses in Indonesian workplaces reflects suboptimal occupational safety and health (K3) implementation, particularly in protecting workers from noise exposure, with discomfort cited as a primary cause. This study investigates factors influencing earplug comfort and proposes user-oriented design improvements. Comfort was measured using the COmfort of hearing PROtection device (COPROD) questionnaire across four dimensions that include physical, functional, acoustic, and psychological, based on responses from 458 users. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) and importance-performance map analysis (IPMA). Results show all four dimensions significantly affect overall comfort, with physical comfort emerging as the most critical yet underperforming factor, making it the primary target for enhancement. Functional comfort also demonstrated below-average performance but with lower relative importance, positioning it as a secondary priority. Key comfort attributes were then converted into functional and technical requirements, informing targeted design interventions to improve earplug performance and user acceptance.